2012
DOI: 10.1016/j.ejso.2012.06.552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of complete cytoreductive surgery and two intraperitoneal chemotherapy techniques in pseudomyxoma peritonei

Abstract: Patients treated for PMP with complete CRS and PIC achieved satisfactory long-term outcome. The most important prognostic factor was histopathological differentiation, but acceptable survival was observed even in patients with aggressive histology and extensive intraperitoneal tumor growth. Administration of EPIC and HIPEC was equally efficacious with respect to long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 117 publications
3
20
0
2
Order By: Relevance
“…The use of cCRS + HIPEC (with mitomycin C) allows to obtain many long-term survival rates in the majority of patients (10-year survival approx. 60%-70%) [7][8][9]. Sugarbaker et al analyzed 385 patients diagnosed with PMP, treated with cCRS (CCR0/CCR1) and HIPEC.…”
Section: Resultsmentioning
confidence: 97%
“…The use of cCRS + HIPEC (with mitomycin C) allows to obtain many long-term survival rates in the majority of patients (10-year survival approx. 60%-70%) [7][8][9]. Sugarbaker et al analyzed 385 patients diagnosed with PMP, treated with cCRS (CCR0/CCR1) and HIPEC.…”
Section: Resultsmentioning
confidence: 97%
“…To date, there have been no prospective studies comparing HIPEC versus EPIC as IPC technique following cytoreduction for appendiceal mucinous neoplasms. A recent retrospective study compared EPIC and HIPEC following optimal cytoreduction and showed no difference in overall or disease free survival .…”
Section: Resultsmentioning
confidence: 99%
“…Modern treatment of PMP consists of CRS and HIPEC [12–14]. All macroscopically visible tumor masses within the peritoneal cavity are surgically removed if possible, and the patients receive subsequent perfusion of the abdominal cavity/peritoneum with heated chemotherapy, while still in general anesthesia [15].…”
Section: Discussionmentioning
confidence: 99%